(3GdOQQ hGdYbjGf ajeG bjOJg ef LegQI GdJjLGfs - (3CHhYHO Gddg eMeO GdJgGej Hf Gdecj Hf YHO GdSdGe QMehf GdMSfjs ((3HdbGSe Hf CMeO GdRjGfj s)
(3ChdgG (B:s
(3hHYO , deG cGf Yde GdMOjK ef CLd GdYdhe bOQkG hcGf ef SfI YdeGA GdMOjK WdH GdELGRI ai GdbOje hGdMOjK hdeG WdY HOQ ehdGfG s
(3BNQgG (B:s
(3hgPG GdbOQ cGa ai gPG ai YPQ GdeNJUQ ajeG CSbW ef Cgd GdHOYI s
(3GNJUQ ajg JCdja TjNg CHj YHO Gddg eMeO Hf GdbGSe GdRjGfi GdeSei HLegQI GdJjLGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B172s
(3Odjd eDQN GdeZQH GdCbUi (B- (3U (B331 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B172 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3O (B724) s
Keywords: (3GdJGQjNs